Model-to-image registration and automatic texture mapping using a video sequence taken by a mini UAV - Iwaszczuk, D.; Helmholz, Petra; Belton, David; Stilla, A. (ISPRS Archives, 2013)
3D city models are used in many fields. Photorealistic building textures find applications such as façade reconstruction, thermal building inspections and heat leakage detection using thermal infrared (TIR) images, quantitative evaluation or study of the materials lying on the object’s surface using multispectral images. Often texturing cannot be done using the same data which was used for 3D reconstruction or textures have to be updated. In such cases co-registration between 3D building models and images has to be carried out. In this paper we present a method for model-to-image matching and texture extraction with best texture selection procedure. We present results for two data sets, first for TIR image sequences taken from a helicopter and second for VIS images taken from an Unmanned Aerial Vehicle (UAV).